Preferences for vehicle ownership and mode choice for commuting trips in Córdoba City - Sartori, Juan José Pompilio (2013)
Fil: Sartori, Juan José Pompilio. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Departamento de Economía y Finanzas; Argentina.